Identification and Validation of the miR/RAS/RUNX2 Autophagy Regulatory Network in AngII-Induced Hypertensive Nephropathy in MPC5 Cells Treated with Hydrogen Sulfide Donors - Qing Ye; Mi Ren; Di Fan; Yicheng Mao; Yi-Zhun Zhu (MDPI AG, 2024)
The balanced crosstalk between miRNAs and autophagy is essential in hypertensive nephropathy. Hydrogen sulfide donors have been reported to attenuate renal injury, but the mechanism is unclear. We aimed to identify and verify the miRNAs and autophagy regulatory networks in hypertensive nephropathy treated with hydrogen sulfide donors through bioinformatics analysis and experimental verification. From the miRNA dataset, autophagy was considerably enriched in mice kidney after angiotensin II (AngII) and combined hydrogen sulfide treatment (H2S_AngII), among which there were 109 differentially expressed miRNAs (DEMs) and 21 hub ADEGs (autophagy-related differentially expressed genes) in the AngII group and 70 DEMs and 13 ADEGs in the H2S_AngII group. A miRNA-mRNA-transcription factors (TFs) autophagy regulatory network was then constructed and verified in human hypertensive nephropathy samples and podocyte models. In the network, two DEMs (miR-98-5p, miR-669b-5p), some hub ADEGs (KRAS, NRAS), and one TF (RUNX2) were altered, accompanied by a reduction in autophagy flux. However, significant recovery occurred after treatment with endogenous or exogenous H2S donors, as well as an overexpression of miR-98-5p and miR-669b-5p. The miR/RAS/RUNX2 autophagy network driven by H2S donors was related to hypertensive nephropathy. H2S donors or miRNAs increased autophagic flux and reduced renal cell injury, which could be a potentially effective medical therapy.